PENDEKATAN GEOEKOSISTEM UNTUK KAJIAN DAYA DUKUNG WILAYAH KEPESISIRAN DI KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - , Adrisal Hena, S.Pi.; , Dr. Langgeng Santosa, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The current research was conducted in the coastal areas of Jailolo Subdistrict of West Halmahera regency, North Maluku province. It is aimed to identify the potential and problems, to assess the carrying capacity based on land suitability, and to formulate the environmental management strategies in coastal areas of Jailolo Subdistrict. This study employs a geoecosystem approach, an approach that unifies the environmental factors that affect the coastal areas. It uses the method of survey, stratified random sampling techniques, quantitative analysis, and spatial modeling using ArcGIS version 9.3 application software, and it formulated a strategy of environmental management using matrices and spatial zoning. The results found 15 units of geoecosystem which are the basis for this research study. Based on the key indicators of an integrated rapid survey, the following potentials have been identified